"Forest medicines, " Kinship Alliances, and Equivocations in the Contemporary Dialogues between Santo Daime and the Yawanawá. (9th August 2022) - Platero, Lígia Duque; de Rose, Isabel Santana
Abstract: In this paper, we describe the spiritual and kinship alliances between heads of an urban Santo Daime church from Rio de Janeiro and some leaders of the Yawanawá people from the Amazonian region. We suggest that these alliances involve exchanges and dialogical relationships that hold different meanings for the diverse social actors that take part in them. Further, we argue that equivocation and functional misunderstandings have an important role in these multidirectional dialogues. Based on this case study, we approach the Yawanawá strategies for capturing otherness, and the insertion of the daimistas in the indigenous sociality networks. We focus especially on the Yawanawá mode of producing kin by capturing non‐indigenous people and their participation in exchange networks that encompass multiple regimes of value. From the daimista point of view, we describe these relationships using the native category of "eclecticism." We suggest that the daimistas attempt to translate the Yawanawá shamanic knowledge and the consumption of the "forest medicines, " experiencing the performance of "becoming indigenous."